CuT 380A IUD Inserted by R-Inserter and Ring Forceps during Postpartum Period A Randomized Clinical Trial, Twelve Months Follow Up: IUD CuT380A yang Dipasang dengan R-inserter dan Klem Cincin pada Masa Pascasalin Uji Klinis secara Random, Pengamatan Dua Belas Bulan - Risanto Siswosudarmo; Nungky Nugroho; Chandra Kurniawan; Yunita Erlina; Dianisa Ikarumi (Indonesian Socety of Obstetrics and Gynecology, 2020)
Abstract Objective: To compare the safety and effectiveness of CuT 380A IUD use inserted by R-inserter compared with those inserted by ring forceps during the postpartum period.Methods: The study was conducted in three puskesmas (community health centre) as affiliated of Sardjito Hospital. Subjects meeting the inclusion and exclusion criteria were recruited to get a 10% proportion expulsion rate difference, type one error 0.05 and type two error 0.20. Insertion using R-inserter was treated while using ring forceps belonged to the control groups. Follow up was carried out one week after the insertion, one month and then monthly for 12months. Rate of the following events i.e.infection, expulsion, pain, bleeding, removal and continuation of use were primary outcomes of interest.Results: A total of 208 eligible subjects were recruited, consisting of 104 subjects using R-inserter and 104 subjects using ring forceps. Cumulative event rates during 12 months follow up were 1%, 4.3%, 3.4%, 10.1% and 4.8% each for infection, expulsion, bleeding, pain, and removal respectively. There was no difference in the rate of infection between the two groups, i.e. 1,0% for each group. There was one pregnancy over 208 subjects giving the overall failure rate of 0.5%. The overall results showed that there were no differences among those events rates (pain, bleeding, removal and continuation) between R-inserter and ring forceps groups. Continuations rate were 93.7%, 93.2%, 90.8%, and 90.8% each for three, six, nine and 12 months follow up respectively.Conclusions: There were no differences in terms of event rates between the use of CuT 380A IUD inserted by R-inserter and ring forceps.Keywords: continuation rate, expulsion, infection, postpartum IUD, R-inserter AbstrakTujuan: Membandingkan keamanan dan keefektifan pemakaian IUD CuT 380A pascasalin yang dipasang dengan R-inserter vs klem cincin.Metode: Penelitian dilakukan di 3 puskesmas di provinsi DIY. Pasien yang memenuhi kriteria kelayakan dimasukkan dalam penelitian ini untuk memenuhi beda proporsi ekspulsi 10%, kesalahan tipe satu 0,05 dan kesalahan tipe dua 0,20. Kelompok uji adalah mereka yang dipasang IUD dengan R-inserter dan kelompok control adalah mereka yang dipasang dengan klem cincin.Follow up dikerjakan setelah satu minggu, satu bulan dan setiap bulan sampai 12 bulan. Infeksi, ekspulsi, nyeri, perdarahan, pelepasan dan kelangsungan pemakaian adalah hasil utama yang diteliti.Hasil: Sebanyak 208 subyek penelitian memenuhi kriteria kelayakan, terdiri atas 104 subyek dipasang dengan R-inserter dan 104 subyek dengan klem cincin. Kejadian kumulatif pada seluruh kasus selama 12 bulan follow up adalah 1%, 4,3%,3,4%, 10,1%, 4,8% masing-masing untuk infeksi, ekspulsi, perdarahan, nyeri, dan pelepasan. Angka infeksi masing-masing sebesar 1% pada kedua kelompok. Terdapat satu kehamilan (0,5%) dari seluruh kasus. Angka kejadian yang lain (nyeri, perdarahan, pelepasan dan kelangsungan pemakaian) tidak menunjukkan perbedaan yang bermakna. Angka kelangsungan pemakaian kumulatif adalah 93,7%, 93,2% 90,8%, dan 90,8% masing-masing pada follow up tiga, enam, Sembilan dan 12 bulan pascapasang.Kesimpulan: Tidak ada perbedaan dalam hal kejadian efek samping antara pemakaian IUD CuT 380A yang dipasang pada masa pascasalin denganR-inserter dan klem cincin.Kata kunci: Angka kelangsungan, ekspulsi, infeksi, IUD pascasalin, pelepasan, R-inserter.